2018
DOI: 10.3126/jnps.v38i1.18659
|View full text |Cite
|
Sign up to set email alerts
|

Scrub Typhus in Children

Abstract: Introduction: Scrub typhus is an acute febrile illness caused by infection with rickettsial bacilli Orientia tsutsugamushi. This was a retrospective observational study to study the clinical profile of paediatric scrub typhus, its associated complications and response to treatmentMaterial and Methods: Record files of all patients diagnosed with positive Weil felix (OXK>1:80) and Scrub IgM positive over a period of one year were analysed. Total of 10 cases were diagnosed as scrub with median age of presentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 7 publications
(13 reference statements)
2
5
0
Order By: Relevance
“…Scrub typhus patients presented with various spectrum of signs and symptoms. Fever was the most common symptom in our study that was similar to other study findings (1,11,12).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Scrub typhus patients presented with various spectrum of signs and symptoms. Fever was the most common symptom in our study that was similar to other study findings (1,11,12).…”
Section: Discussionsupporting
confidence: 92%
“…Similar seasonal variation has been reported by other authors (6,7,8). The majority of the cases were reported by Zainab et al, and Naveen et al, between June and November (1,9). In another study, maximum number of cases was observed between the month of May and August (10).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations